Assessment of Effects of Prebiotics Supplementation on Feed Intake, Egg and Serum Cholesterol Levels in White Leghorn Layers - Sheoran, Nancy; Sihag, Sajjan; Maan, N.S. (Indian Journal of Animal Nutrition, 2018)
The present study was undertaken to evaluate the effect of supplementation of graded levels of prebiotics on feed intake, egg yolk cholesterol, serum cholesterol levels and internal egg quality parameters in White Leghorn layers. An experiment trial was run for a period of 16 weeks with eighty White Leghorn layers in the age group of 22-23 weeks of age were allotted randomly to four dietary treatments having 4 replications with 5 birds each. The control diet (T1) was formulated as per the BIS (2007) meeting the requirements for laying phase of the hens in the age group of 22-38 weeks. In addition, the birds in treatments T2, T3 and T4 were supplemented with prebiotics (containing mannonoligosacchrides of the Saccharomyces cell wall-47 g, formic acid (85%)-32 g,HSCAS upto 1 kg) @ 0.5, 1.0 and 2.0 g/kg of feed, respectively. Laying hens receiving prebiotics exhibitedimprovement in feed conversion ratio of 3.83 and 7.34% in treatment groups T3 and T4, respectively compared to control. The prebiotics supplementation showed positive effect on internal egg quality parameters viz. albumen index, yolk index and Haugh unit in layers supplemented with graded levels of the prebiotics ascompared to the control group. Maximum increase of 1.92% in albumen index and 2.06% in Haugh unit was observed in treatment T4 as compared to T1. However, no significant effect was observed for yolk index. Also, a significant (P